Initial results on the variation of whistle characteristics of bottlenose dolphins from two neighbouring regions of the Mediterranean Sea: Northern Ionian and Southern Adriatic Sea - Akkaya, Aylin; Awbery, Tim; Medcalf, Kirsty; Lyne, Patrick; Cipriano, Giulia; Alvarenga, Morgana; İsrapilova, Leyla; Atalan, Yağmur; Eikelenboom, Olivier; Ricci, Pasquale; Crugliano, Roberto; Papale, Elena; et al. (Frontiers in Marine Science, 2023)
Bottlenose dolphins have a complex vocal repertoire that varies depending on behavioral context, social structure, group composition and anthropogenic pressures. This current study describes the whistle characteristics of bottlenose dolphins for the first time in the South Adriatic Sea while assessing the potential differences between whistle characteristics of geographically separated dolphins within neighbouring waters of the North Ionian Sea. The results show that whistle characteristics were similar between Taranto Gulf and Boka Bay, despite their spatial differences. The mean peak frequency was 10kHz for each study location while the mean minimum and maximum frequency ranged from 7 to 14kHz. The average duration of whistles was 500 milliseconds. These results share similarities with previous literature, although several studies reported slightly different mean peak frequencies, ranging up to 15kHz in the neighbouring waters of Croatia and Italy. Further, harmonics were produced and formed in 40% of the whistles in Taranto Gulf and 30% of the whistles in Boka Bay. A high incidence of harmonics has previously been associated with behavioral states (i.e., travelling) and with certain types of marine traffic (i.e., fishing vessels). Therefore, it is important to collect simultaneous data on the visual behavior of the focal group as well as document the type and density of marine traffic within the proximity of the dolphins to have an in-depth understanding of vocal behavior. Despite the similarities of whistle characteristics of Taranto and Boka Bay, the whistle contours showed notable variations. Upsweep whistles were the most regularly produced whistle type in each location, which coincides with previous studies in the Mediterranean Sea. However, the least produced whistle had a concave contour in Taranto and was flat in Boka Bay. Previous studies have confirmed that flat whistles account for the least produced whistle contour in the Mediterranean Basin. Examining the whistle characteristics and the variation in whistle contours provides an in-depth understanding of the behavioral complexity as well as its elasticity in the presence of pressure. Therefore, future studies need to include behavior, group composition, noise levels, and human presence to enable an effective understanding of variation in whistle characteristics of bottlenose dolphins.